Ideology and Power in the Viking and Middle Ages - Gro Steinsland, Jón Viðar Sigurðsson, Jan Erik Rekdal and Ian Beuermann (brill, 2011)
The present book is the result of research carried out at the Centre for Advanced Study (CAS) in Oslo during the academic year 2007–08. An international group of scholars from different disciplines—history of religion, medieval history and celtology—attempted to gain a better understanding of the ideological aspects of rulership in the Nordic countries during the Viking and early Middle Ages. The most important research is now presented in this book, Ideology and Power in the Viking and Middle Ages. Scandinavia, Iceland, Ireland, Orkney and the Faeroes. We have incurred a great debt to the Centre for Advanced Study for the stimulating and luxurious research conditions we enjoyed during our project there. Together, the volume’s individual chapters thus represent our interdisciplinary project: methodological approaches and professional interests differ, but our common research revolved around the relation between power and religion. We have then also chosen to publish our results as chapters of a common book, rather than as a collection of articles. All authors have contributed with much more than their texts. Even though the length of the stay at the Centre for Advanced Study varied for individual participants, we were all engaged in an exciting, challenging, and fruitful discussion on the power of rulers and religion from the Viking to the Middle Ages. At the end of a year of intensive research into a common project, we have all developed a deeper, perhaps new, understanding of the important relations between power, ideology, myths and rituals in a common northern European warrior culture of the late Viking Age and the transition to Christianity and the Middle Ages. The main hypothesis, that important elements of the pre-Christian ideology of rulership survived into the early Middle Ages, transformed or even simply transferred, seems to have been strengthened by our research. This book presents some of our main results, and hopes to initiate further discussion. Four of the participants have been responsible for the continuation and publication of our research: Prof. Gro Steinsland, Prof. Jón Viðar Sigurðsson, Prof. Jan Erik Rekdal, and Dr. Ian Beuermann.